RELIGIOUS SYMBOLISM IN THE WORKS OF GRAPHIC ARTIST-NARENDRA SRIVASTAVA - Thakur, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Religious symbolism implies the use of unique symbols by a particular religion, that describe anything pertaining to its culture and psyche, including archetypes, events, natural phenomena or even the art that evolved in that land over a period of time. All religions of the world, irrespective of how ancient or modern they are, use symbols to help create a resonant ethos, which in turn, reflects the moral values, teachings and culture of that society. The concept of religious symbolism is very ancient and may well have had its roots from the start of mankind itself. This can be seen in the series of paintings with the word ‘DHARMA’ painted in 1984, done basically for calendar, depicting six great religions of world Hinduism, Buddhism, Christianity, Islam, Confucianism, and Judaism by renowned graphic designer, eminent artist, and art educationist, Narendra Srivastava. By seeing these drawings it seems that artist must be highly religious which is not true because he had used the word graphically only. He did it for his pleasure of creating something new out of it, which makes his artworks very creative. These paintings do have some religious symbolism in it, which the artist had graphically depicted in a very innovative and impressive style.